(untitled) (Journal of Civil Engineering Researchers, 2025)
Nowadays, with the aging of old structures and the advancement of construction technologies, demolition projects for outdated structures have seen significant growth. this paper focuses on demolition methods in detail. In a case study conducted in Iran, this paper evaluates the demolition methods for a concrete silo using the Analytical Hierarchy Process (AHP) to select the optimal method based on cost, time, and quality (safety). Time evaluation is performed using MSP software, while cost assessment for each method is estimated based on resources allocated to the activities within the Work Breakdown Structure (WBS) of each approach. Safety evaluation employs a combined application of the AHP and Data Envelopment Analysis (DEA) methods. Required data for constructing pairwise comparison matrices were gathered through questionnaires completed by domain experts. The results reveal that the demolition method using concrete wire saws scores the highest among the methods evaluated. Furthermore, based on modeling results in Sap2000 software, it is shown that single-stage toppling of the silo by removing its main columns is not feasible. Subsequently, the site layout design and lifting plan calculations for the selected method were carried out. All outcomes were compared with real-life execution, and the project’s success demonstrated the effectiveness of the chosen method due to comprehensive consideration of all construction management aspects of a demolition project. This paper is written with the aim of simplifying technical concepts in the management of demolition methods.